Effect of colorant solutions on the color stability of provisional prosthetic materials - Ítalo Alisson da Fonsêca Costa; Emilena Maria Castor Xisto Lima (Universidade Estadual de Campinas, 2018)
Aim: To evaluate the color stability of acrylic and bis-acrylic resins after immersion in 3 staining solutions. Methods: Forty-eight samples (10 x 2 mm) of each provisional restorative material (Duralay, Dencrilay, Structur 2 and Protemp 4) were fabricated and distributed into four groups (n = 12): G1 - distilled water (control group); G2 - a cola flavored soft drink; G3 - wine and G4 - coffee. The specimens were immersed for seven days at 37°C in the solutions, which were changed every 24 hours. The color of all specimens was measured with a spectrophotometer (VITA Easyshade Advance) before (T0) and after immersion (T1), and the color changes (ΔE) were calculated. Nonparametric Kruskal-Wallis tests were used, followed by Dunn's test with a significance level of 5%. Results: For the acrylic resins (Duralay and Dencrilay), the largest color change values were obtained in group G4 - coffee, whereas in the bis-acrylic resins (Protemp 4 and Structur 2), the largest color difference was observed in groups G3 - wine and G4 - coffee. The acrylic resins showed statistically significantly less color change than the bis-acrylic resins. Conclusions: The coffee and the wine promoted larger color changes in the provisional prosthetic materials tested in this study. The acrylic resins showed more color stability than the bis-acrylic resins.